Transcultural Music-Making in Contemporary Music Ensembles: Five Approaches in Germany, the Netherlands, Uzbekistan and Turkey - Heldt, Katja (Circuit, 2018)
The present article describes the approaches of five ensembles specialized in transcultural music-making in the context of contemporary music in Germany, the Netherlands, Uzbekistan and Turkey. While facing similar underlying conceptual and practical challenges in the process of combining different musical traditions and cultural backgrounds, such as the question of how to merge oral and notated traditions, tuning systems or musical perceptions, and their presentational performance practices, each ensemble suggests different strategies of implementation, depending on their political, historical and geographical circumstances.The article examines the way in which music derives representational functions within processes of affiliation, delimitation, representation and identity construction.